Draft Annual Plan 1988-89 Volume : XI Hill Areas Government of Assam - Planning Commission (Planning Commission, 1988)
During the period, construction of buildings for establishment of 100 bedded District Hospital at Haflong was completed. Construction of buildings for establishment of, a 30 bedded T.B. Hospital at Haflong, a building for a Medical Store, barrack for accommodation of 20 Nurses, quarter for five married Nurses, and quarter for 20 Grade IV staff at Haflong Civil Hospital was sanctioned. At Diphu Civil Hospital, construction of eight quarters for doctor were taken up.
Government of Assam, Development Commissioner for Hill Areas
Government of Assam, Development Commissioner for Hill Areas